Rhythmic Gymnastics Workshop Singapore 16-19 September 2009 - Krasilshchikov, Oleksandr (Pusat Pengajian Sains Kesihatan, 2009)
Main objective of the workshop is to promote health and appreciation of the beauty of body movements by means of Rhythmic Gymnastics. Specific objectives are improving the posture, keeping children in good physical condition, developing agility and flexibility, improving creativity and developing music culture, confidence and quality of self expression.